Absorption and emission properties of various substituted cinnamic acids and cinnamates, based on TDDFT investigation. Issue 4 (4th June 2012) - Promkatkaew, Malinee; Suramitr, Songwut; Karpkird, Thitinun; Ehara, Masahiro; Hannongbua, Supa; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract Absorption and emission properties of the hydroxy‐, nitro‐, and fluoro‐group substituted at the ortho‐, meta‐, and para‐positions of cinnamic acids (1A–9A) and cinnamates (1E–9E) were investigated using the density functional theory (DFT) and time‐dependent DFT (TDDFT) calculations. The ground (S0)‐ and excited (S1)‐state geometries were obtained at the B3LYP/6‐31G(d) and TD‐B3LYP/6‐31G(d) methods, respectively. On the basis of the optimized structures of the S0‐ and S1‐states, the TDDFT calculations with B3LYP and CAM‐B3LYP functionals were performed to compute the absorption and emission energies of the various substituted cinnamic acids and cinnamates. The solvent effect was examined by the polarizable continuum model in methanol solution. As result, all compounds had the local minimum at the planar structure conformation due to π‐conjugation. The characteristics of the absorption spectra for cinnamic acid and cinnamate derivatives were satisfactorily reproduced by TDDFT method in gas phase and in methanol solution in both peak position and intensity. The emission from the local minimum in the planar structure was calculated for various substituted cinnamic acids and cinnamates. The results obtained by TDDFT investigation provide a useful insight into the detailed information on the optical and electronic properties of these compounds and a useful tool for designing and developing the superior UV absorber compounds. © 2012 Wiley Periodicals, Inc.